2017
DOI: 10.1007/s11356-017-0580-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of chromophoric dissolved organic matter parallel factor analysis fluorescence and polycyclic aromatic hydrocarbons in natural surface waters

Abstract: Polycyclic aromatic hydrocarbons (PAHs), a large group of persistent organic pollutants (POPs), have caused wide environmental pollution and ecological effects. Chromophoric dissolved organic matter (CDOM), which consists of complex compounds, was seen as a proxy of water quality. An attempt was made to understand the relationships of CDOM absorption parameters and parallel factor analysis (PARAFAC) components with PAHs under seasonal variation in the riverine, reservoir, and urban waters of the Yinma River wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The composition and distributions of CDOMs were impacted by the environmental factors (water quality, soil, vegetation, land use, and rainfall) and could generally affect the absorption and fluorescence of CDOMs at certain wavelengths [ 20 ]. Generally, the absorption coefficient a CDOM (350) is used to characterize the concentration of CDOMs [ 7 , 29 ] and a CDOM (254) can be used as a proxy for characterizing the aromaticity of CDOMs [ 7 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The composition and distributions of CDOMs were impacted by the environmental factors (water quality, soil, vegetation, land use, and rainfall) and could generally affect the absorption and fluorescence of CDOMs at certain wavelengths [ 20 ]. Generally, the absorption coefficient a CDOM (350) is used to characterize the concentration of CDOMs [ 7 , 29 ] and a CDOM (254) can be used as a proxy for characterizing the aromaticity of CDOMs [ 7 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…To determine the dissolved organic carbon (DOC) concentrations, all of the water samples were filtered through a pre-combusted Whatman GF/F (1825-047) filter (0.45 μm) under low vacuum and were measured by the Shimadzu TOC-VCPN analyzer. Chlorophyll a (Chl-a) was extracted from the filtered (0.45-µm Whatman GF/F) sample using a 90% acetone solution; subsequently, the concentrations were determined using a UV spectrophotometer (UV-2006 PC, Shimadzu, Kyoto, Japan); the detailed process can be found in Song et al (2012) [ 20 ]. The total suspended matter (TSM), inorganic suspended matter (ISM), and organic suspended matter (OSM) were determined by gravimetrical analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, various studies have found that PAHs in foods were mainly produced by high-temperature pyrolysis, gas combustion or direct contact with open fire (such as baking, grilling [ 8 ], drying [ 9 ] and smoking [ 10 ]), mainly due to the incomplete combustion of organic matter [ 11 , 12 , 13 ] or the high-temperature degradation of fat in barbecue products [ 14 ].…”
Section: Introductionmentioning
confidence: 99%